Diálogos e Cartas Pedagógicas em Círculos de Cultura: ressignificando a formação continuada de professoras e professores em ensino de Astronomia - Borges, Elizandra Freitas Moraes (2024)
Continuing teacher training in Brazil is a complex and challenging field. With regard to the one that deals with astronomical knowledge, the scenario becomes even more challenging. Continuing training proposals, in general, are characterized by a prescriptive and dissertative character, silencing subjects within the scope of their own training. Therefore, the present investigation aimed to analyze which essential elements, emerging from the extension course “Astronomy at school in the context of culture circles, should be considered for the construction of permanent, participatory and contextualized training for teachers who teach Astronomy at school. To this end, the research is based on the discussion of the continued training of teachers who teach Astronomy in elementary school, based on the problematization substantiated in the Freirean Theory, which drives critical-problematizing thinking, providing knowledgeable subjects with dialogical training in Astronomy. Its premises are dialogue, knowledge from experience, participation, coding/decoding, action/reflection/action, transformation and autonomy. The research has a qualitative approach, of the collaborative research-training type in the Brazilian context. To this end, the meetings were held as Culture Circles – based on episodes of the story “Joãozinho da Maré” written by Rodolpho Caniato – with 31 teachers from a school affiliated with the city hall of Goiânia, in a videoconference environment, given the exceptional nature of the context of Covid-19. The transcriptions of the recorded dialogues and the Pedagogical Letters produced by the teachers during the culture circles were analyzed using Discursive Textual Analysis (ATD) and the source of metatext production that revealed what the teachers thought for participatory and contextualized training in teaching Astronomy. The research results indicate that participatory and contextualized training needs to be organized based on the needs of teachers in the teaching of Astronomy, the relationship between teachers and the teaching of Astronomy, the complexity of teaching Astronomy and the need from rebuilding the bond with Nature to understanding the topic, as well as sky observation practices and local and ancestral Astronomy.